Proton-detected C,H correlation NMR techniques for the complete assignment of all proton and carbon resonances of a cyclic peptide - Hofmann, Mechtild (Magnetic resonance in chemistry : MRC, 1989)
Copyright © 1989 John Wiley & Sons, Ltd.